Integrative review on psychological and social risk and prevention factors of eating disorders including anorexia nervosa and bulimia nervosa: seven major theories. Issue 11 (November 2022) - Zanella, Elise; Lee, Eunro
Abstract: Across the globe, disordered eating disorders alarmingly have increased by over 30% in the general public, as characterised by a wide range of eating, shape and weight concerns. Subsequent physical, functional, social, and mental health issues significantly burden society, conveying various personal sufferings to affected individuals. Disordered eating behaviours and cognitions can increase to clinical severity, such as anorexia nervosa and bulimia nervosa. The present study critically reviewed over 100 major papers on disordered eating to integrate theoretical underpinnings and explore practical insights. The review resulted in identifying seven major theories concerning the development and persistence of disturbed eating behaviour. These include self-esteem theory, interpersonal theory, emotion regulation theory, executive function theory, social neuroscience theory, theory of mind, and trans-diagnostic theory. Furthermore, depression, anxiety, social norms and family functioning also emerged as major psychological and social correlates of disordered eating. The results further suggested significant research gaps and inconsistencies, including directional ambiguity between self-esteem and body dissatisfaction, self-esteem and depression, and executive functioning and eating, as well as mixed findings pertaining to theory of mind deficits, such as perspective taking and emotion recognition, and family functioning. Prospective empirical studies should incorporate these complexities and investigate underlying multiple psychological mediation mechanisms, preferably with experimental designs and longitudinal studies for further causal explanations. Abstract : Eating disorders; Anorexia; Bulimia; Self-esteem; Trans-diagnostic theory; Emotion regulation; Executive function; Theory of mind.